Pancasila Moral Values for Nation Building in the Globalization Era - Siregar, Tiara Tiffany (International Journal of Students Education, 2025)
The purpose of writing this article is to describe and explain how Pancasila can play a role, be implemented, and actualized in the context of globalization, with the aim of increasing morality in an effort to build and advance the nation. This research uses a qualitative method or descriptive approach, taking sources from various literatures. The results of the analysis show that globalization brings changes in people’s lives, and Pancasila has an important role in responding and adapting to new information, especially to maintain the identity of the Indonesian nation, especially the younger generation, to remain connected to the values of Pancasila. This can done through organizing informal education programs, campaigns social, and activities a community that promotes the values of Pancasila. With work same strong between all party related, we can ensure that generation young Indonesians grow become a leader with character, integrity and care to nation and state. Therefore, the replanting of Pancasila values is important to build and advance the nation.